Secular trends and latitude gradients in the male-female ratio at birth in Yugoslavia and the ex-Yugoslavian States - Grech, Victor (Acta Medica, 2013)
BACKGROUND: Latitude gradients and secular trends in Europe and North America have been found in the male-female ratio at birth (M/F: male births divided by total births) which approximates 0.515. METHODS: Annual national data for Yugoslavia and the post-Yugoslavia States for male and female live births were obtained from the World Health Organisation and analysed with contingency tables. RESULTS: This study analysed 22,020,729 live births. There was a increasing trend in M/F prior to the breakup of the former Yugoslavia (1950-1990, p = 0.002), followed by a decreasing trend after 1990 (p = 0.02). A latitude gradient was also noted, with more males being born in southern, warmer latitudes (p < 0.0001). There was an overall excess of 42,753 male births based on an anticipated M/F of 0.515. CONCLUSION: M/F is decreasing in this region, similar to the rest of Europe and North America. A latitude gradient is also present with more males being born in warmer (more Southern) latitudes (p < 0.0001), even in this small region and over the short time-frame studied.
Keywords: sekularismus; lidé; Female; mužské pohlaví; Birth Rate; Sex Ratio; Geography; Male; Yugoslavia; poměr pohlaví; Secularism; porodnost; ženské pohlaví; zeměpis; Jugoslávie; Humans